Autonomous Supramolecular Interface Self‐Healing Monitored by Restoration of UV/Vis Absorption Spectra of Self‐Assembled Thiazole Layers. Issue 36 (30th May 2019) - Hupfer, Maximilian L.; Herrmann‐Westendorf, Felix; Kaufmann, Martin; Weiß, Dieter; Beckert, Rainer; Dietzek, Benjamin; Presselt, Martin
Abstract: Longevity of complex organic devices critically depends on the supramolecular integrity of the constituting layers and interfaces. Because the latter are soft matter, they can structurally respond to perturbation of their supramolecular structure by relaxing back to a thermodynamically favorable state. To use this response for self‐healing of optoelectronically active layers and particularly interfaces, the degraded dyes in these layers need to be exchanged with non‐degraded ones. Here, we present a dye layer interfaced between a solid surface and a dye reservoir that autonomously self‐heals after photo‐degradation of single molecules to restore its optical function. Surface sensitive in situ photothermal deflection spectroscopy reveals that this supramolecular self‐healing approach critically depends on the thermodynamic stability of the layer, the chemical change of the dye upon degradation, and the medium dissolving the degraded dye and providing the reservoir dyes. Hence, the interplay of these parameters is key to successfully using this supramolecular self‐healing approach to thin layers and interfaces in organic device for increased sustainability of organic optoelectronics and related fields. Abstract : Healing power : Scheme of supramolecular self‐healing of an optoelectronically active membrane that is in contact with a reservoir for to exchange degraded and pristine dyes. Inset on the right shows the actual chemical structure of the used amphiphilic thiazole with dipolar chromophore. The electrostatic potential φ is plotted at the van der Waals surface.